Update in Pediatric Musculoskeletal Infections: When It Is, When It Isn't, and What to Do. Issue 9 (September 2016) - Arkader, Alexandre; Brusalis, Christopher; Warner, William C.; Conway, James H.; Noonan, Kenneth
Abstract : Musculoskeletal infections, including osteomyelitis, septic arthritis, and pyomyositis, are a substantial cause of morbidity in children and adolescents. The increased virulence of infectious agents and the increased prevalence of antimicrobial-resistant pathogens, particularly methicillin-resistant Staphylococcus aureus, have resulted in a more complicated clinical course for diagnosis and management, which is evidenced by an increased length of hospital stays, incidence of complications, and number of surgical interventions. Musculoskeletal infections are a challenge for surgeons because they vary substantially in their presentation and in their required treatment, which is based on the causative organism, the location of the infection, and the age of the patient. The necessity for a prompt diagnosis is complicated by several diseases that may mimic musculoskeletal infection, including transient synovitis, autoimmune arthritis, and tumors. Recent innovations in diagnosis and management have provided surgeons with new options to differentiate musculoskeletal infections from these rapidly evolving disease pathologies. As diagnostic and treatment modalities improve, collaboration among surgeons from multiple disciplines is required to develop evidence-based clinical practice guidelines that minimize the effect of musculoskeletal infection and optimize clinical outcomes for patients.